Building innovation capability in the less favoured regions - university collaboration as a tool - Kati-Jasmin Kosonen (European Regional Science Association (ERSA), 2002)
Know-how, innovations and learning have become key issues in a new regional development logic and there has emerged a need for implementing new kinds of academic institutions creating and applying new knowledge. This means that economic actor's or players have to be part of the knowledge formulation and networks where the most essential knowledge is built and formulated. Regional or local knowledge environment has become more important. This kind of learning and knowledge supporting, knowledge and human resources pointed environment is based on the local institutional settings and the relationships and partnerships in and between different institutions. The relationships and the range of institutions, which are concerned as members of the development cluster, can be weak or strong due the passed development path. Both the institutions and the interaction between them are needed. The innovation capacity is formed by different institutions and relationships between them supporting the individual organisation and those capability to innovate as well as relationships to the resources outside the region. If there in a certain region are not enough formal and informal development institutions and interaction between them, actors find it more difficult to transform information to new knowledge and innovations. If the regions do not have development agencies, higher education institutions etc. the possible information channels can be weak on the one hand between different actors in the region and on the other hand to and from the region. This kind of regions can often be seen as "less favoured regions" or "institutionally thin" regions. Therefore national, regional and local authorities and development organisations (including universities) are trying to support innovations through different knowledge networks and new type of collaboration. Universities are now seen as a mechanism through which broad social and economical change towards a knowledge economy would be achieved. Universities are thus a part of local innovation supporting system or innovation supporting "milieu". Universities are a part of the network of building and maintaining local/ regional innovation capacity and therefore affecting to local innovation capability. The aim of the paper is to study how universities through collaboration and localisation (establishing regional joint-institutions) can take part to local innovation networks and how have the roles of universities changed in these institutional building processes. Furthermore the interest is in the issue of how capable university based development actors in the less favoured (or institutionally thin) regions are activating local innovation capacities? What kind of collaboration models has universities and other development actors formed in the less favoured region for improving local innovation capability and last, how have universities managed their changed role? The paper is based on a qualitative case study from Pori and Seinäjoki sub-regions (in Finland). These regions are examples of disadvantaged regions, which are building a strong institutional base of Higher education institutions and university-based knowledge transfer systems in order to emphases the interaction between region and these higher education (and research) institutions collaboratively.
Keywords: 330